Dynamics of Health Care Financing and Spending in Serbia in the XXI Century - Krstic, Kristijan; Janicijevic, Katarina; Timofeyev, Yuriy; Arsentyev, Evgeny V.; Rosic, Gvozden; Bolevich, Sergey; Reshetnikov, Vladimir; Jakovljevic, Mihajlo B. (Frontiers in Public Health, 2019)
Serbia is an upper-middle income Eastern European economy. It has inherited system of health provision and financing, which is a mixture of Soviet Semashko and German Bismarck models. So far, literature evidence on long-term trends in health spending remains scarce on this region. Observational descriptive approach was utilized relying on nationwide aggregate data reported by the Republic Health Insurance Fund (RHIF) and the Government of Serbia to the WHO office. Consecutively, the WHO Global Health Expenditure Database1 was used. Long-term trends were extrapolated on existing data and underlying differences were analyzed and explained. The insight was provided across two distinctively different periods within 2000–2016. The first period lasted from 2000 till 2008 (the beginning of global recession triggered by Lehman Brothers' bankruptcy). This was a period of strong upward growth in ability to invest in health care. Spending grew significantly in terms of GDP share, national and per capita reported expenditures. During the second period (2009–2016), after the beginning of worldwide economic crisis, Serbia was affected in a way that its health expenditure growth in PPP terms slowed down effectively fluctuating around plateau values from 2014 to 2016. Serbia health spending showed promising signs of steady growth in its ability to invest in health care. Consolidation marked most of the past decade with certain growth rates in recent years (2017–2019), which were not captured in these official records. The future national strategy should be devised to take into account accelerated population aging as major driver of health spending.